Toothbrushing and gingival recession - Litonjua, Luis A.; Andreana, Sebastiano; Bush, Peter J.; Cohen, Robert E. (International dental journal, 2003)
Aim: To review the hypothesis that toothbrushing leads to gingival recession. Gingival recession develops due to anatomical and pathological factors. The prevalence of recession is dependent on the age and characteristic of the population because it usually presents in individuals with periodontal disease or those who practise zealous or improper oral hygiene methods. Gingival trauma and gingival abrasion from toothbrushing is thought to progress directly to gingival recession. Case studies documenting recession from toothbrush trauma are speculative. Short-term studies suggest that gingival trauma and gingival abrasion may result from toothbrushing, but the direct relationship between traumatic home care and gingival recession is inconclusive. Long-term studies remain elusive or do not support the development of recession following toothbrushing. Nevertheless, tooth abrasion may be an integral part in the aetiology of recession. Toothbrush abrasion also may cause wear at the cemento-enamel junction resulting in the destruction of the supporting periodontium leading to recession.